Individual program of running activity of track-and-field athletes during training sessions to improve sports skills in the preparation for a cross season - Маленюк, Тетяна (Slobozhanskyi Herald of Science and Sport, 2017)
Tetiana Maleniuk Purpose: to develop an individual program of running work of athletes, specializing in running for long distances, during the preparation for the autumn-winter cross season. Material & Methods: study was conducted in the group of improving sports skill in athletics of the faculty of physical education of the Pedagogical University. It was attended by 4 athletes, specializing in running for long distances at the age of 19–20 years. Results: the individual program of running work of a track and field athlete on the basis of a system of mesocycles and microcycles is presented. The structure and content of running work in each mesocycle is disclosed. Trends in the growth of running loads in mesocycles are determined. Conclusion: proved the effectiveness of the introduction of this program in the training process of training athletes for the cross season on the basis of improving the result of the competitive exercise and improving athletic qualifications for track and field cross.